In-situ growth carbon nanotube reinforced carbon fiber composite material carbon slide strip
The catalyst-free chemical vapor deposition method generates carbon nanotubes and carbon particles in situ on the carbon fiber slide, solving the problems of uneven dispersion and unsolid bonding, improving the mechanical, conductive and frictional properties of the slide, achieving significant performance Improve adaptability to mass production.
Patent Information
- Application Number
- CN202411334205.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The mechanical, conductive and frictional properties of existing carbon fiber slides need to be further improved, and the problems of uneven dispersion and poor bonding of carbon nanotubes in composite materials limit their excellent performance.
The chemical vapor deposition method without catalyst is used to generate carbon nanotubes and carbon particles in situ on the surface of carbon fiber and graphite particles. Through alternating deposition technology of high and low temperatures, a special distribution structure is formed, which improves the mechanical, conductive and friction wear properties of the slider and promotes graphite. Transformation.
It significantly improves the flexural strength, compressive strength, impact toughness and electrical conductivity of the skateboard, reduces friction and wear, is suitable for large-scale production, and has excellent product performance.
Smart Images

Figure CN119161202A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon slide bar made of in-situ grown carbon nanotube reinforced carbon fiber composite material, belonging to the technical field of material preparation for electric locomotives. Background Art
[0002] The pantograph slide plate came into being with the emergence of electric locomotives. As the core component for electric locomotives to obtain current from the contact wire, its material has evolved from pure metal, pure carbon slide plate, powder metallurgy and metal-impregnated carbon slide plate. At present, the materials of electric locomotive slide plates are mainly pure carbon slide plates and metal-impregnated carbon slide plates. Pure carbon slide plates are obtained by mixing, kneading, extruding and then roasting graphite, additives and binders. Because of the excellent self-lubricating properties of carbon itself, it greatly reduces its wear on the contact wire, which greatly extends the life of the contact wire. However, the pure carbon slide plate itself has poor mechanical properties, and its impact toughness is only 0.2-0.5 J·cm -2 In actual operation, due to breakage, cracking and eccentric wear, its service life is very short.
[0003] Based on the pure carbon skateboard, researchers began to obtain metal-impregnated carbon skateboards by pressurizing and impregnating molten Cu into porous carbon matrices. This skateboard improved the mechanical properties of the material to a certain extent and greatly improved the conductivity of the carbon skateboard, but the wear at the docking site was aggravated, and due to the non-wetting problem between carbon and copper, the impact toughness of the skateboard was still low. During operation, fractures and block drop still occurred, and the wear amount increased instead of decreased. SHUNICHI KUBO et al. found that during the current-carrying friction between the metal-impregnated carbon skateboard and the copper contact line, the wear amount would increase significantly with the increase of current density, and the uneven distribution of carbon and copper in micro-regions also made it easier for this type of skateboard to generate arcs during operation, causing melt splashing and evaporation of the copper inside the skateboard.
[0004] Table 1 Performance of pure carbon slider and metal-impregnated carbon slider
[0005]
[0006] Carbon / carbon composites are carbon fiber reinforced carbon matrix composites with outstanding advantages such as high specific strength and specific modulus, as well as excellent thermal physical properties and friction and wear properties. They are usually obtained by weaving carbon fiber preforms, densifying preforms, and high-temperature graphitization treatment. Their mechanical properties, thermal conductivity, electrical conductivity, and friction and wear properties can be adjusted. Domestic and foreign scholars have reported a lot on the research of C / C composites as skateboards. Mulang Hongzhi et al. investigated the use of C / C composite skateboards on 223 series vehicles running at a speed of 130km / h on the Sanyo main line and found that the friction surface of the skateboard was smooth and without defects. Yoshitaka Kubota et al. studied the performance of metal Cu impregnated C / C composites and found that the resistivity of C / C-Cu composites can be as low as 0.5μΩ·m or less, and the friction film formed during the friction process is conducive to reducing self-wear. The wear of carbon skateboards is positively correlated with arc energy. High-strength carbon fibers cannot reduce the wear of carbon skateboards, but heat treatment can change the graphitization degree of carbon in the composite material, thereby affecting the wear of the material.
[0007] Jia Lixiao and others compared the performance of C / C composite materials with that of pure carbon skateboards imported from Germany and found that the resistivity of C / C composite materials was comparable to that of imported materials, but the compressive strength, bending strength and impact toughness were increased by 2-3 times. In addition, arc suppression oil, which can reduce the occurrence of arcs, was added to C / C composite materials. The oil can also significantly reduce and stabilize the friction coefficient of C / C composite materials, reducing the wear rate of C / C composite materials to 1 / 3 of the original.
[0008] Lin Yang et al. used the reactive melt deposition method to infiltrate Cu into C / C composites to prepare C / C-Cu composites. The study found that the copper in the C / C-Cu composites was distributed in the matrix in a three-dimensional network, with a resistivity as low as 0.7 μQ·m and an impact toughness of 2.2 J·cm -2 The above results show that, with the increase of carbon fiber content, the friction coefficient and wear volume are reduced, which is attributed to the formation of a Cu2O friction film on the surface of the C / C-Cu composite material. Gao Yuan et al. studied the current-carrying friction and friction characteristics of the copper composite material reinforced with fine-woven carbon fiber puncture fabric prepared by low-pressure impregnation method and found that the friction and wear performance of the composite material is better than that of pure Cu.
[0009] However, the mechanical, electrical and friction properties of existing carbon fiber skateboards need to be further improved. Carbon nanotubes are made of curled carbon nanotube sheets. They are the material with the highest specific strength that can be prepared at present. They have good electrical conductivity and high thermal conductivity. Doping with trace amounts of carbon nanotubes can greatly improve the strength, elasticity, fatigue resistance, isotropy, electrical conductivity and thermal conductivity of composite materials, so they have potential application value in many fields. Adding an appropriate amount of carbon nanotubes to carbon fibers is not only beneficial to improving the electrical conductivity of the material, but also effectively improving its friction properties. However, the cost and dispersion difficulty of carbon nanotubes limit their application.
[0010] Chinese invention patent CN 109484190A (a process for preparing a carbon fiber reinforced carbon pantograph slide) discloses a method for preparing carbon nanotubes. The invention discloses a process for preparing a carbon fiber reinforced carbon pantograph slide, comprising the following steps: step 1: mixing graphene powder with conductive epoxy resin and curing agent to form a paste; step 2: applying the paste obtained in step 1 on the surface of the carbon fiber tube; step 3: placing the carbon fiber tube after applying the paste into a carburizing furnace for carburizing treatment to obtain a carburized porous body; step 4: placing the carburized porous body obtained in step 3 into an impregnation solution containing silver ions for a period of time, taking it out, and drying it. Step 5: Put the carburized porous body obtained in step 4 into a carbonization furnace for carbonization to obtain a carbon fiber reinforced carbon tube body; Step 6: Mix graphite powder, titanium powder and furan resin to form a colloid; Step 7: Use the colloid obtained in step 6 to glue multiple carbon fiber reinforced carbon tube bodies together to form a carbon fiber reinforced carbon slider embryo; Step 8: Cover the surface of the carbon fiber reinforced carbon slider embryo obtained in step 7 with graphite paper, and then put it into a hot isostatic press for hot pressing and curing; Step 9: Put the carbon fiber reinforced carbon slider embryo that has been cured in step 8 into a carbonization furnace again for carbonization treatment to obtain a carbon fiber reinforced carbon slider. The pantograph slide plate prepared by this carbon fiber reinforced carbon pantograph slide plate preparation process has strong mechanical strength, good lubrication performance and impact resistance, less wear on the contact network wire, and good wear resistance.
[0011] Chinese invention patent CN106699181B (a method for preparing a pantograph carbon slider material using graphene oxide) discloses a method for preparing a pantograph carbon slider material using graphene oxide, comprising the following steps: mixing graphene oxide, semi-reinforced carbon black, graphite powder and crushed, ground and sieved asphalt coke as aggregate for preparing the carbon slider; adding a binder to the aggregate, and then kneading to obtain a paste; pre-pressing the paste; and calcining the pre-pressed paste to finally obtain a material suitable for the pantograph carbon slider. The present invention only requires one calcination to obtain a carbon bar material that meets the requirements, and the production cycle is short. The pantograph carbon slider prepared by graphene oxide provided by the present invention has the advantages of good electrical conductivity, high thermal conductivity, strong friction and wear resistance, and low raw material cost.
[0012] Chinese invention patent CN 117658660 A (a mesophase pitch carbon fiber reinforced pantograph carbon slide plate and its preparation method) discloses a mesophase pitch carbon fiber reinforced pantograph carbon slide plate and its preparation method, the preparation method comprising the following steps: (1) modifying the mesophase pitch carbon fiber with an active agent, and then ultrasonically dispersing and vacuum drying to obtain the modified mesophase pitch carbon fiber; (2) dry-mixing calcined pitch coke, needle coke, artificial graphite powder, N339 carbon black and modified mesophase pitch carbon fiber to obtain dry powder; (3) adding a molten binder to the dry powder in step (2), and then kneading, rolling, and back-mixing to form a material column; (4) extruding, calcining, and pressurizing the material column with metal copper to obtain the mesophase pitch carbon fiber reinforced pantograph carbon slide plate. The pantograph carbon slide plate prepared by the present invention has low resistivity and good mechanical properties, impact toughness and thermal stability.
[0013] Chinese invention patent CN 117403090 A (a graphene-modified copper-based carbon locomotive pantograph slide plate and its preparation method) discloses a graphene-modified copper-based carbon locomotive pantograph slide plate and its preparation method, which belongs to the field of nanomaterials. The method obtains an electric locomotive pantograph slide plate by graphene modification of copper composite metallurgical powder. The preparation method evenly disperses solids with large specific gravity differences, and evenly and stably disperses defect-free graphene with very light specific gravity and easy to agglomerate in the copper-based carbon composite powder with large specific gravity, thereby ensuring the mixing uniformity of the graphene-modified copper-based carbon composite powder. Compared with existing products, the high-speed electric locomotive pantograph slide plate prepared by the method has greatly improved electrical conductivity and good arc burn resistance; greatly improved friction reduction and wear resistance, strong environmental adaptability, and more than twice the product life; good self-lubrication, no damage to the conductor; simple production equipment, short production cycle, simple process, suitable for large-scale production.
[0014] Carbon nanotubes have high surface activity. They can be effectively dispersed in liquid or molten materials by shear mixing, grinding, cavitation and other methods. The interaction between carbon nanotubes and dispersants can also be improved to a certain extent by adding surfactants or surface modification methods, so as to achieve maximum dispersion. However, as the amount added increases, dispersion becomes more difficult. In addition, the improvement of the mechanical properties of the composites is not ideal when carbon nanotubes are directly mixed with epoxy resin and asphalt. This is mainly because the tubes of carbon nanotubes are very smooth and have weak binding ability with organic matter. When subjected to shear force, they are prone to relative sliding with the matrix, so that their excellent performance is not fully manifested in composite materials. In order to solve the problem of uneven dispersion of carbon nanofibers and weak bonding with the matrix, some scholars have proposed the idea of in-situ growth of carbon nanofibers on carbon fibers. Among all the preparation methods of carbon nanofibers, the CVD method is more suitable for in-situ growth on carbon fibers. The in-situ growth process includes three steps: first, surface treatment of carbon fibers to increase active points; second, loading catalysts on the surface of carbon fibers; and third, in-situ growth of carbon nanofibers by CVD method.
[0015] At present, the methods for in-situ preparation of carbon nanotubes on powder mainly include arc discharge method, plasma method, laser evaporation method, catalytic cracking method and chemical vapor deposition method. Carbon nano gas phase catalytic growth requires catalyst particles, carbon source and heating. Commonly used catalysts are transition metals of iron, cobalt, nickel and their alloys or metal oxide particles. The catalytic cracking method is to crack carbon-containing compounds (CO, CH4, C2H2, etc.) into carbon atoms at a relatively high temperature (600-1000°C). Under the action of transition metal catalysts, carbon atoms adhere to the surface of catalyst particles to form carbon nanotubes. The equipment and process of this method are relatively simple, and it is suitable for large-scale production of carbon nanotubes. The carbon nanotube content in the product is relatively high, but the key is the preparation and dispersion of the catalyst. Chemical vapor deposition is a method of using nano-scale transition metals such as Fe, Co, Ni or their alloys and compounds as catalysts. At a relatively low temperature (500-1300°C), a certain proportion of hydrocarbons (such as methane, acetylene, benzene, etc.) and carrier gas (usually argon) are introduced to catalytically crack the carbon source gas. The carbon nanotubes are then decomposed, diffused and precipitated on the catalyst particles. This is a simple, easy and high-yield method, and is currently the most commonly used method for preparing carbon nanotubes.
[0016] Whether it is catalytic cracking or chemical vapor deposition, the most important step in the preparation of carbon nanotubes is the preparation and dispersion of the catalyst. The main catalysts currently used are transition metal-supported solid catalysts, and the transition metals are generally Fe, Co, Ni and their alloys, and SiO2, Al2O3, MgO, zeolite and other high-temperature resistant oxides are used as carriers. Lyu et al. successfully used C2H2 to synthesize single-walled carbon nanotubes, and used Fe / Mo / Al2O3 catalysts to prepare high-purity and high-yield single-walled carbon nanotubes at 950°C. However, the catalyst is difficult to remove, which also limits the use of the carrier.
[0017] Chinese invention patent CN104388847B (Method for preparing carbon nanotubes by chemical vapor deposition) discloses a method for preparing carbon nanotubes, i.e., preparing carbon nanotubes by chemical vapor deposition, comprising the following steps: placing a substrate with a catalyst into an oxygen-free reactor, making the temperature of the substrate reach 500-1200°C, and then introducing a carbon-containing substance into the reactor to obtain carbon nanotubes; wherein the catalyst is a metal or a metal compound.
[0018] So far, there is no prior art on the process of in-situ generation of carbon nanotubes in a carbon fiber composite skateboard without adding a catalyst, nor is there any report on in-situ alternating deposition of carbon particles and carbon nanotubes. Summary of the invention
[0019] During the process of technology development, it was found that under certain conditions, carbon nanotubes can be generated in situ on the surface of carbon fibers and graphite particles by chemical vapor deposition without a catalyst. The present invention was formed based on this discovery.
[0020] In view of the deficiencies in the prior art, the present invention provides a method for preparing an in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider which does not require a catalyst, has a simple preparation process, a short process flow, low cost, and is suitable for large-scale production.
[0021] The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider of the present invention is the first to design in-situ generated carbon nanotubes and carbon particles with a special distribution structure. The mechanical, electrical conductivity and friction and wear properties of the slider are greatly improved; and through the in-situ growth characteristics of carbon nanotubes and carbon particles, the graphitization transformation of the densified asphalt under carbonization and graphitization is promoted, achieving a significant increase in the graphitization rate of the final product.
[0022] The present invention discloses an in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider, comprising a carbon fiber needle-punched integral felt, a coating layer M covering the inside and outside of the carbon fiber needle-punched integral felt, and carbon coated on M;
[0023] The M includes the following four structures:
[0024] Structure 1M is a carbon nanotube and carbon particles generated in situ by chemical vapor deposition, and the carbon nanotubes and carbon particles are alternately distributed.
[0025] Structure 2 M is carbon nanotubes and carbon particles generated in situ by chemical vapor deposition, and the carbon particles are coated on the carbon nanotubes;
[0026] Structure three: M is a carbon nanotube layer generated in situ by chemical vapor deposition and N, wherein the N is composed of in situ generated carbon particles and carbon nanotubes; the N is coated on the carbon nanotubes;
[0027] Structure 4: M is a carbon nanotube layer and N generated in situ by chemical vapor deposition, wherein N is composed of carbon particles and carbon nanotubes generated in situ; the carbon nanotube layer and N are alternately distributed;
[0028] The carbon coated on M is cracked carbon prepared by an impregnation carbonization process; the carbon fiber needle-punched integral felt comprises a carbon fiber braid and a conductive wear-resistant filler;
[0029] The carbon fiber braided body comprises at least one of a pure carbon fiber braided body and a three-dimensional composite braided body composed of carbon fiber and metal mesh;
[0030] The conductive wear-resistant filler includes graphite powder, or at least one of graphite powder and copper powder.
[0031] Preferably, no catalyst is required when preparing M.
[0032] In the carbon fiber needle-punched integral felt, the particle size of graphite particles is 50-800 μm, and the diameter of carbon fibers is 5-100 μm.
[0033] In the coating layer M, the particle size of the carbon particles A is 20-600 nm.
[0034] In the coating layer M, the carbon nanotubes have a diameter of 5-30 nm and a length of 30 nm-3 μm.
[0035] In the coating layer M, the thickness of a single coating layer is less than or equal to 6 μm.
[0036] The present invention provides a method for preparing an in-situ grown carbon nanotube reinforced pure carbon fiber carbon slider, wherein the pure carbon fiber slider (i.e., the carbon slider does not contain metal) is prepared by the following steps:
[0037] Step 1
[0038] A single layer of 0° non-weft carbon cloth, carbon fiber mesh, graphite powder, short carbon fiber (30-100 mm long), a single layer of 90° non-weft carbon cloth, a carbon fiber mesh, graphite powder, and a single layer of 0° non-weft carbon cloth are sequentially stacked in a cycle, and a carbon fiber bundle is introduced perpendicular to the layering direction by a relay needle punching method to make a carbon fiber bundle with a density of 0.2-0.8 g / cm 32.5D carbon fiber needle-punched integral felt;
[0039] Step 2
[0040] The carbon fiber needle-punched integral felt obtained in step 1 is fixed and placed in a heating furnace, and subjected to a pre-high temperature heat treatment at 1500-2100° C. under a protective atmosphere to obtain an integral felt after the pre-high temperature heat treatment;
[0041] Step 3: Prepare the M layer
[0042] The whole felt obtained in step 2 after the previous high-temperature heat treatment is repeatedly subjected to high- and low-temperature chemical vapor deposition, and carbon particles / carbon nanotube layers are alternately deposited on the surface of graphite particles, carbon fibers, etc., to obtain a chemical vapor deposition pure carbon fiber slider;
[0043] Step 4: Asphalt impregnation-carbonization treatment
[0044] The chemical vapor deposition pure carbon fiber slider obtained in step 3 is machined according to the designed size, and after reserving the processing allowance, it is asphalt impregnated-carbonized until the density is 1.7-2.0 g / cm 3 High-density impregnation-carbonization treatment slide material;
[0045] Step 5
[0046] The impregnation-carbonization treated sliding strip obtained in step 4 is subjected to post-high temperature graphitization treatment to obtain an in-situ grown carbon nanotube reinforced pure carbon fiber carbon sliding strip.
[0047] The present invention discloses a method for preparing an in-situ grown carbon nanotube reinforced metal carbon fiber composite material carbon slider, wherein the metal carbon fiber composite material carbon slider is prepared by the following steps:
[0048] Step A
[0049] A single layer of 0° non-weft carbon cloth, carbon fiber mesh, graphite powder, copper material, a single layer of 90° non-weft carbon cloth, carbon fiber mesh, graphite powder, copper material, and a single layer of 0° non-weft carbon cloth are sequentially stacked in a cycle, and a carbon fiber bundle is introduced perpendicular to the layering direction by a relay needle punching method to prepare a 2.5D carbon fiber composite material needle-punched integral felt with a density of 0.6 to 2.6 g / cm3;
[0050] Step B Preparation of M layer
[0051] The carbon fiber composite needle-punched integral felt obtained in step 1 is fixed and placed in a heating furnace, and high and low temperature chemical vapor deposition is repeated multiple times to alternately deposit carbon particles / carbon nanotube layers on the surfaces of graphite particles, carbon fibers, etc., to obtain a chemical vapor deposition metal type carbon fiber composite sliding strip having a density 1.5-2.2 times that of the integral felt in step A;
[0052] Step C: Asphalt impregnation-carbonization treatment
[0053] The chemical vapor deposited pure carbon fiber slider obtained in step B is machined according to the designed size, and after reserving the processing allowance, it is asphalt impregnated and carbonized until a high-density impregnated and carbonized in-situ grown carbon nanotube reinforced metal carbon fiber composite carbon slider with a density of 1.02-1.15 times that of the one obtained in step 2 is obtained.
[0054] The present invention provides a method for preparing an in-situ grown carbon nanotube reinforced metal carbon fiber composite material carbon slider.
[0055] The copper material is selected from one of copper powder, copper mesh and short copper wire. In the 2.5D carbon fiber needle-punched integral felt, the mass percentage of graphite powder is 1% to 10%; the mass percentage of copper material is 10-90%;
[0056] The present invention provides a method for preparing a carbon slider made of in-situ grown carbon nanotube reinforced carbon fiber composite material. When preparing the M layer,
[0057] The in-situ chemical vapor deposition temperature is 850℃~1100℃;
[0058] The in-situ chemical vapor deposition time is 83 to 420 hours;
[0059] The carbon source gas used is selected from at least one of propylene, natural gas and methane.
[0060] The diluent gas used is selected from at least one of nitrogen and hydrogen.
[0061] The volume ratio of the carbon source gas to the dilution gas is 0.8-1.2:2.8-3.2.
[0062] The present invention provides a method for preparing an in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider. When preparing the M layer, in-situ vapor deposition at different temperatures is performed in a temperature alternating manner, comprising the following steps:
[0063] (1) First, heat to 850-950℃ and keep warm for 3-20h.
[0064] (2) Raise the temperature to 950-1050°C and keep it at this temperature for 50-200 hours.
[0065] (3) Finally, raise the temperature to 1080-1100°C and keep it at this temperature for 30-200 hours.
[0066] The present invention provides a method for preparing an in-situ grown carbon nanotube reinforced pure carbon fiber carbon slider.
[0067] In the pre-high temperature pretreatment of step 2:
[0068] The protective atmosphere is selected from one of argon atmosphere and nitrogen atmosphere.
[0069] During the pre-high temperature treatment, the control time is 3-10h.
[0070] During the pre-high temperature treatment, the pressure in the furnace is controlled to be 0.101-0.11MPa;
[0071] In the post-high temperature pre-treatment of step 5:
[0072] The post-high temperature graphitization treatment temperature is 2000-2400°C.
[0073] The post-high temperature graphitization treatment time is 5 to 10 hours.
[0074] The post-high temperature graphitization treatment protective atmosphere is selected from one of an argon atmosphere and a nitrogen atmosphere.
[0075] The post-high temperature graphitization treatment furnace pressure is 0.12 MPa.
[0076] The present invention provides a method for preparing an in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider, wherein the asphalt impregnation-carbonization treatment comprises the following steps:
[0077] After the preparation of the M layer is completed, the obtained sample is placed in an asphalt impregnation liquid at 40-80°C, and is impregnated for 1-3 hours by pressurized impregnation. The temperature is then raised to 220-260°C for curing for 2.5-3.5 hours, and the impregnation pressure is 1.5 MPa. After the curing is completed, the carbonization treatment is carried out at a carbonization temperature of 1000°C, a single carbonization treatment time of 40-60 hours, and a carbonization pressure of 0.1 MPa. The impregnation / curing / carbonization treatment is repeated until a density of 1.6-2.0 g / cm is obtained. 3 The high-density C / C composite material is prepared; the polymer impregnation liquid used in the polymer impregnation-carbonization treatment is an asphalt solution.
[0078] In the present invention, carbon nanotubes are deposited in situ on the surface of carbon fiber without using a catalyst by a simple in situ chemical vapor deposition process. In addition, carbon nanotubes and carbon nanotubes can be deposited in situ alternately on the surface of carbon fiber and graphite particles by adjusting the deposition temperature and deposition time.
[0079] In the present invention, the principle of generating carbon nanotubes and carbon particles is as follows: low-temperature chemical vapor deposition is used to make graphite and carbon fibers form oxides at low temperatures (oxygen comes from the overall felt weaving raw materials and the adsorption of oxygen during the process), and then the oxides are reacted at the growth temperature of chemical vapor deposition of 850 to 950°C to form intermediates of their oxides, and nanowires are obtained through disproportionation reaction, that is, the grown carbon nanotubes only form flocs or plates, and the carbon atoms only form aggregates of short carbon nanowires. In the present invention, the disproportionation reaction of oxides can be used to obtain carbon nanowires / tubes without a catalyst; when the chemical vapor reaction temperature is further increased to 950 to 1050°C, the carbon nanotubes are filamentous and grow evenly on the surface of graphite / silicon particles, and the diameter of the grown carbon nanotubes is uniform (about tens of nanometers). When the chemical vapor reaction temperature reaches 1100°C, almost no carbon nanotubes grow, but only amorphous carbon nanoparticles are deposited on the surface of graphite and carbon fiber (at 1070-1100°C, there are both graphite particles and short nanotubes, but at this time, the proportion of graphite particles is greater than that of short carbon nanotubes). By using alternating high and low temperature deposition, carbon particles or carbon fibers alternately coated with carbon particles / carbon nanotubes can be formed in the carbon fiber. Compared with the carbon nanotubes added during the preparation of the felt, this in-situ grown carbon nanotube can not only be effectively fixed on the surface of carbon fiber and graphite particles, but also solve the problem of uneven dispersion of carbon nanotubes, fully realizing the advantages of carbon nanotubes such as excellent electrical conductivity, thermal conductivity, strengthening the matrix and improving wear resistance.
[0080] In the present invention, the principle of achieving rapid carbonization or graphitization is as follows: inside the carbon fiber composite material, after the carbon nanotubes are grown in situ on the carbon surface, if furan resin is used for impregnation, due to the large amount of impregnation, it is difficult to completely carbonize it at 850°C. Only through high-temperature graphitization treatment can graphitization be achieved, but the decomposition and graphitization time of furan resin is longer than that of asphalt, so the graphitization degree after high-temperature graphitization only reaches 87%. Moreover, furan resin is a thermosetting material, which will not soften after heating, and will not achieve further densification of carbon fiber in the carbonization and graphitization stages. If it is used to directly impregnate and carbonize to prepare a metal-type carbon fiber composite material carbon skateboard, due to incomplete decomposition of the resin, the skateboard has poor conductivity and deteriorates friction performance. However, by using asphalt impregnation-carbonization at above 1000°C, rapid carbonization or graphitization can be achieved, and the graphitization degree can reach 93% after high-temperature graphitization treatment above 2000°C, and asphalt is a thermoplastic material, which will soften after heating, and further densification of carbon fiber can be achieved in the carbonization and graphitization stages. If the metal carbon fiber composite material carbon skateboard is prepared by direct impregnation carbonization with asphalt, the conductivity of the carbon skateboard is improved and the friction performance is improved because the asphalt is completely decomposed and carbonized at this temperature. The preparation process of the present invention is simple, and the product has excellent mechanical, conductive and friction properties, and is suitable for large-scale industrial application and production.
[0081] In the case of not introducing metal, the flexural strength of the product obtained by the present invention is greater than 120MPa, which can reach 130-145MPa after optimization; the compressive strength is 370-390MPa, and the impact toughness is 1.9-2.0J·cm -2 , resistivity as low as 16.8~17.1μΩ·m, contact line wear ratio less than or equal to 0.008mm 2 / 10,000 vehicle-kilometers, the height wear ratio of the skateboard is less than or equal to 0.25mm / 10,000 vehicle-kilometers, and the weight wear ratio of the skateboard is less than or equal to 25g / 10,000 vehicle-kilometers.
[0082] In the case of introducing metal Cu, the flexural strength of the obtained product is greater than 135MPa, and can reach 138-152MPa after optimization; the compressive strength is 290-295MPa, and the impact toughness is 1.1-1.2J·cm -2 , resistivity as low as 2.5~2μΩ·m, contact line wear ratio is less than or equal to 0.018mm 2 / 10,000 vehicle-kilometers, the height wear ratio of the skateboard is less than or equal to 0.42mm / 10,000 vehicle-kilometers, and the weight wear ratio of the skateboard is less than or equal to 31g / 10,000 vehicle-kilometers. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 A process flow chart of a method for preparing a pure carbon fiber slider with in-situ deposited carbon nanotubes provided by an embodiment of the present invention;
[0084] Figure 2 A process flow chart of a method for preparing a metallic carbon fiber composite material carbon slider with in-situ deposition of carbon nanotubes provided in an embodiment of the present invention;
[0085] Attached Figure 3 This is the TEM morphology of carbon nanotubes grown by in-situ deposition on the carbon fiber surface in Example 1 of the present invention.
[0086] Depend on Figure 1 It can be seen that the present invention mainly includes key steps such as pre-heat treatment, high and low temperature alternating chemical vapor deposition, asphalt impregnation-carbonization, and post-heat treatment.
[0087] Depend on Figure 2 It can be seen that the present invention mainly includes the main steps of high-low temperature alternating chemical vapor deposition, asphalt impregnation-carbonization and the like.
[0088] Depend on Figure 3 It can be seen that a large number of carbon nanotubes are deposited on the surface of carbon fiber after alternating high and low temperature (1050-1100°C) chemical vapor deposition. DETAILED DESCRIPTION
[0089] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the technical solution recorded in the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0090] Comparative Example 1
[0091] The density is 0.35g / cm 3 The 2.5D carbon fiber needle-punched integral felt was used as a preform, and a density of 1.5g / cm was prepared by chemical vapor deposition process. 3 The C / C composite material with a density of 1.8 g / cm was prepared through three resin impregnation-carbonization processes. 3 The C / C composite material was subjected to 2300℃ high temperature heat treatment and machining to obtain pure carbon fiber sliders.
[0092] The pure carbon fiber slider in this comparative example is mainly prepared by the following steps:
[0093] (1) PAN type T700 (12K) carbon fiber produced by Toray Co., Ltd. of Japan was used to make a mesh and a flat cloth, and the mass ratio of the flat cloth to the mesh was ensured to be 8:2. A single layer of 0° flat cloth, a mesh layer, a 90° flat cloth, a mesh layer, and graphite (150 μm, an addition amount of 10 wt%) were cyclically stacked in sequence, and then a relay needle punching method was used to make a density of 0.6 g / cm 3 Carbon fiber preform.
[0094] (2) Using graphite tooling, the preform is subjected to a high temperature heat treatment at 1600°C in an argon protective atmosphere for 8 hours. The protective atmosphere is argon and the pressure is slightly positive (i.e., slightly exceeding the 0 mark on the vacuum pressure gauge);
[0095] (3) Natural gas was used as the carbon source gas, hydrogen was used as the diluent gas, and the volume ratio of natural gas to hydrogen was 1:3. Thermal gradient chemical vapor deposition was used to deposit pyrolytic carbon on the preform at 950 °C. After deposition for 100 h, the density of C / C was 0.85 g / cm 3 The C / C composite material was rotated 90° with the longitudinal centerline as the axis and then deposited for 200 h to obtain a density of 1.5 g / cm 3 C / C composite materials.
[0096] (4) The C / C composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and furan resin is used as the impregnating agent and treated by a high-pressure impregnation process. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 200°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment at a carbonization temperature of 850°C. After three cycles, the product density reaches 1.8g / cm 3 .
[0097] (5) The obtained product was placed in a high-temperature heat treatment furnace and treated at 2300°C for 6 hours, using argon as the protective gas to obtain a pure carbon fiber slider. The specific properties are shown in Tables 2 and 3.
[0098] The flexural strength, compressive strength, impact toughness, resistivity and Shore hardness of pure carbon fiber and metal carbon fiber composite carbon sliders made of chemical vapor deposited carbon particles and in-situ deposited carbon nanotubes are compared, and the results are shown in Table 2. The two materials are made into carbon fiber slide plates for pantographs, and current-carrying friction is carried out with the CTMH150 contact line. The running speed is 120km / h, the current is 500A, and the normal pressure between the slide plate and the contact line is 70N±10N. The friction and wear properties are shown in Table 3.
[0099] Comparative Example 2
[0100] The density is 0.35g / cm 3 , a 2.5D carbon fiber needle-punched integral felt with carbon nanotubes added was used as a preform, and a density of 1.5 g / cm was prepared by chemical vapor deposition process. 3 The C / C composite material with a density of 1.8 g / cm was prepared through three resin impregnation-carbonization processes. 3 The C / C composite material was subjected to 2300℃ high temperature heat treatment and machining to obtain pure carbon fiber sliders.
[0101] The pure carbon fiber slider in this comparative example is mainly prepared by the following steps:
[0102] (1) PAN type T700 (12K) carbon fiber produced by Toray Co., Ltd. of Japan was used to make a mesh and a flat cloth, and the mass ratio of the flat cloth to the mesh was ensured to be 8:2. A single layer of 0° flat cloth, a mesh layer, a 90° flat cloth, a mesh layer, graphite (150 μm, an addition amount of 10 wt%), and carbon nanotubes (diameter 20 nm, an addition amount of 10 wt%) were sequentially stacked in a cycle, and then a relay needle punching method was used to make a density of 0.35 g / cm 3 Carbon fiber preform.
[0103] (2) Using graphite tooling, the preform is subjected to a high temperature heat treatment at 1600°C in an argon protective atmosphere for 8 hours. The protective atmosphere is argon and the pressure is slightly positive (i.e., slightly exceeding the 0 mark on the vacuum pressure gauge);
[0104] (3) Natural gas was used as the carbon source gas, hydrogen was used as the diluent gas, and the volume ratio of natural gas to hydrogen was 1:3. Thermal gradient chemical vapor deposition was used to deposit pyrolytic carbon on the preform at 950 °C. After deposition for 100 h, the density of C / C was 0.85 g / cm 3 The C / C composite material was rotated 90° with the longitudinal centerline as the axis and then deposited for 200 h to obtain a density of 1.5 g / cm 3 C / C composite materials.
[0105] (4) The C / C composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and furan resin is used as the impregnating agent and treated by a high-pressure impregnation process. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 200°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment at a carbonization temperature of 850°C. After three cycles, the product density reaches 1.8g / cm 3 .
[0106] (5) The obtained product was placed in a high-temperature heat treatment furnace and treated at 2300°C for 6 hours, using argon as the protective gas to obtain a pure carbon fiber slider. The specific properties are shown in Tables 2 and 3.
[0107] In the process of preparing carbon fiber preforms by relay needle punching, carbon nanotubes are difficult to disperse due to their fine particle size, and many of them leak out from the felt.
[0108] Comparative Example 3
[0109] The density is 0.35g / cm 3 The 2.5D carbon fiber needle-punched integral felt was used as a preform, and a density of 1.5g / cm was prepared by chemical vapor deposition process. 3 The C / C composite material with a density of 1.8 g / cm was prepared through three asphalt impregnation-carbonization processes. 3 The C / C composite material was subjected to 2300℃ high temperature heat treatment and machining to obtain pure carbon fiber sliders.
[0110] The pure carbon fiber slider in this comparative example is mainly prepared by the following steps:
[0111] (1) PAN type T700 (12K) carbon fiber produced by Toray Co., Ltd. of Japan was used to make a mesh and a flat cloth, and the mass ratio of the flat cloth to the mesh was ensured to be 8:2. A single layer of 0° flat cloth, a mesh layer, a 90° flat cloth, a mesh layer, graphite (150 μm, an addition amount of 10 wt%), and carbon nanotubes (diameter 20 nm, an addition amount of 10 wt%) were sequentially stacked in a cycle, and then a relay needle punching method was used to make a density of 0.35 g / cm 3 Carbon fiber preform.
[0112] (2) Using graphite tooling, the preform is subjected to a high temperature heat treatment at 1600°C in an argon protective atmosphere for 8 hours. The protective atmosphere is argon and the pressure is slightly positive (i.e., slightly exceeding the 0 mark on the vacuum pressure gauge);
[0113] (3) Natural gas was used as the carbon source gas, hydrogen was used as the diluent gas, and the volume ratio of natural gas to hydrogen was 1:3. Thermal gradient chemical vapor deposition was used to deposit pyrolytic carbon on the preform at 950 °C. After deposition for 100 h, the density of C / C was 0.85 g / cm 3 The C / C composite material was rotated 90° with the longitudinal centerline as the axis and then deposited for 200 h to obtain a density of 1.5 g / cm 3 C / C composite materials.
[0114] (4) The C / C composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment. The carbonization temperature is 1000°C, the single carbonization treatment time is 50h, and the carbonization pressure is 0.1MPa. After three cycles of impregnation / curing / carbonization treatment, the product density reaches 1.8g / cm 3 .
[0115] (5) The obtained product was placed in a high-temperature heat treatment furnace and treated at 2300°C for 6 hours, using argon as the protective gas to obtain a pure carbon fiber slider. The specific properties are shown in Tables 2 and 3.
[0116] Comparative Example 4
[0117] The density is 0.35g / cm 3 , a 2.5D carbon fiber needle-punched integral felt with carbon nanotubes added was used as a preform, and a density of 1.5 g / cm was prepared by chemical vapor deposition process. 3 The C / C composite material with a density of 1.8 g / cm was prepared through two asphalt impregnation-carbonization processes. 3The C / C composite material was subjected to 2300℃ high temperature heat treatment and machining to obtain pure carbon fiber sliders.
[0118] The pure carbon fiber slider in this comparative example is mainly prepared by the following steps:
[0119] (1) PAN type T700 (12K) carbon fiber produced by Toray Co., Ltd. of Japan was used to make a mesh and a flat cloth, and the mass ratio of the flat cloth to the mesh was ensured to be 8:2. A single layer of 0° flat cloth, a mesh layer, a 90° flat cloth, a mesh layer, graphite (150 μm, an addition amount of 10 wt%), and carbon nanotubes (diameter 20 nm, an addition amount of 10 wt%) were sequentially stacked in a cycle, and then a relay needle punching method was used to make a density of 0.35 g / cm 3 Carbon fiber preform.
[0120] (2) Using graphite tooling, the preform is subjected to a high temperature heat treatment at 1600°C in an argon protective atmosphere for 8 hours. The protective atmosphere is argon and the pressure is slightly positive (i.e., slightly exceeding the 0 mark on the vacuum pressure gauge);
[0121] (3) Natural gas was used as the carbon source gas, hydrogen was used as the diluent gas, and the volume ratio of natural gas to hydrogen was 1:3. Thermal gradient chemical vapor deposition was used to deposit pyrolytic carbon on the preform at 950 °C. After deposition for 100 h, the density of C / C was 0.85 g / cm 3 The C / C composite material was rotated 90° with the longitudinal centerline as the axis and then deposited for 200 h to obtain a density of 1.5 g / cm 3 C / C composite materials.
[0122] (4) The C / C composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment. The carbonization temperature is 1000°C, the single carbonization treatment time is 55h, and the carbonization pressure is 0.1MPa. After two cycles of impregnation / curing / carbonization treatment, the product density reaches 1.8g / cm 3 .
[0123] (5) The obtained product was placed in a high-temperature heat treatment furnace and treated at 2300°C for 6 hours, using argon as the protective gas to obtain a pure carbon fiber slider. The specific properties are shown in Tables 2 and 3.
[0124] In the process of preparing carbon fiber preforms by relay needle punching, carbon nanotubes are difficult to disperse due to their fine particle size, and many of them leak out from the felt.
[0125] Comparative Example 5
[0126] The density is 0.6g / cm 3 The 2.5D carbon fiber copper mesh needle-punched integral felt is used as a preform, and a metal-type carbon fiber composite material carbon slider is prepared through a chemical vapor deposition process and a three-time resin impregnation-carbonization process.
[0127] The metal carbon fiber composite material carbon slider in this comparative example is mainly prepared by the following steps:
[0128] (1) First, a portion of PAN type T700 (12K) carbon fiber bundles produced by Toray Co., Ltd. of Japan is woven into a non-woven fabric, and another portion of the T700 carbon fiber bundles is cut into short fibers of 30-100 mm in length, and dispersed together with copper powder and graphite powder to form a mesh. Secondly, 0° non-woven carbon cloth, carbon fiber mesh, copper mesh, 90° non-woven carbon cloth, carbon fiber mesh, copper mesh, and 0° non-woven carbon cloth are cyclically stacked in sequence, and copper wire and / or carbon fiber bundles are introduced perpendicular to the layering direction by a relay needle punching method to form a non-woven fabric with a volume content of 5-15%, a mesh with a volume content of 5-15%, a copper mesh and / or copper wire with a volume content of 5-30%, and a density of 0.6 g / cm 3 Composite felt body.
[0129] (2) Using propylene as the carbon source gas and hydrogen as the diluent gas, the volume ratio of natural gas to hydrogen is 1:2, and thermal gradient chemical vapor deposition is used to deposit pyrolytic carbon on the preform at 1000°C. After deposition for 120 hours, the material is rotated 90° with the center line of the length as the axis, and then deposited for another 250 hours to obtain a C / Cu composite material.
[0130] (3) The C / Cu composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and furan resin is used as the impregnating agent and treated by a high-pressure impregnation process. Before impregnation, the sample should be preheated, the impregnation temperature is 100°C, the impregnation pressure is 2MPa, and the holding time is 2h. After that, the temperature is raised to 200°C and kept warm for about 5h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment at a carbonization temperature of 850°C for 60h. After three cycles, the density reaches 2.0-4.0 / cm 3 The specific properties of the metal type carbon fiber composite material carbon slider are shown in Table 2 and Table 3.
[0131] Comparative Example 6
[0132] The density is 0.7g / cm 3 , a 2.5D carbon fiber copper mesh needle-punched integral felt with added carbon nanotubes is used as a preform, and a metal-type carbon fiber composite carbon slider is prepared through a chemical vapor deposition process and a three-time resin impregnation-carbonization process.
[0133] The metal carbon fiber composite material carbon slider in this comparative example is mainly prepared by the following steps:
[0134] (1) First, a portion of PAN-type T700 (12K) carbon fiber bundles produced by Toray Co., Ltd. of Japan is woven into a non-woven fabric, and another portion of the T700 carbon fiber bundles is cut into short fibers of 30-100 mm in length, and dispersed together with copper wire (diameter 10 μm), graphite powder (150 μm), and carbon nanotubes (diameter 20 nm) to form a mesh. Secondly, 0° non-woven carbon cloth, carbon fiber mesh, copper mesh, 90° non-woven carbon cloth, carbon fiber mesh, copper mesh, and 0° non-woven carbon cloth are cyclically stacked in sequence, and copper wire and / or carbon fiber bundles are introduced perpendicular to the layering direction by a relay needle punching method to form a non-woven fabric with a volume content of 5-15%, a mesh with a volume content of 5-15%, a copper mesh and / or copper wire with a volume content of 5-30%, and a density of 0.7 g / cm 3 Composite felt body.
[0135] (2) Using propylene as the carbon source gas and hydrogen as the diluent gas, the volume ratio of natural gas to hydrogen is 1:2, and thermal gradient chemical vapor deposition is used to deposit pyrolytic carbon on the preform at 1000°C. After deposition for 120 hours, the material is rotated 90° with the center line of the length as the axis, and then deposited for another 230 hours to obtain a C / Cu composite material.
[0136] (3) The C / Cu composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and furan resin is used as the impregnating agent and treated by a high-pressure impregnation process. Before impregnation, the sample should be preheated, the impregnation temperature is 100°C, the impregnation pressure is 2MPa, and the holding time is 2h. After that, the temperature is raised to 200°C and kept warm for about 5h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment at a carbonization temperature of 850°C for 60h. After three cycles, the density reaches 2.0-4.0 / cm 3 The specific properties of the metal type carbon fiber composite material carbon slider are shown in Table 2 and Table 3.
[0137] In the process of preparing carbon fiber preforms by relay needle punching, carbon nanotubes are difficult to disperse due to their fine particle size, and many of them leak out from the felt.
[0138] Comparative Example 7
[0139] The density is 0.6g / cm 3 The 2.5D carbon fiber copper mesh needle-punched integral felt is used as a preform, and a metal-type carbon fiber composite carbon slider is prepared through a chemical vapor deposition process and two asphalt impregnation-carbonization processes.
[0140] The metal carbon fiber composite material carbon slider in this comparative example is mainly prepared by the following steps:
[0141] (1) First, a portion of PAN type T700 (12K) carbon fiber bundles produced by Toray Co., Ltd. of Japan is woven into a non-woven fabric, and another portion of the T700 carbon fiber bundles is cut into short fibers of 30-100 mm in length, and dispersed together with copper powder and graphite powder to form a mesh. Secondly, 0° non-woven carbon cloth, carbon fiber mesh, copper mesh, 90° non-woven carbon cloth, carbon fiber mesh, copper mesh, and 0° non-woven carbon cloth are cyclically stacked in sequence, and copper wire and / or carbon fiber bundles are introduced perpendicular to the layering direction by a relay needle punching method to form a non-woven fabric with a volume content of 5-15%, a mesh with a volume content of 5-15%, a copper mesh and / or copper wire with a volume content of 5-30%, and a density of 0.6 g / cm 3 Composite felt body.
[0142] (2) Using propylene as the carbon source gas and hydrogen as the diluent gas, the volume ratio of natural gas to hydrogen is 1:2, and thermal gradient chemical vapor deposition is used to deposit pyrolytic carbon on the preform at 1000°C. After deposition for 120 hours, the material is rotated 90° with the center line of the length as the axis, and then deposited for another 250 hours to obtain a C / Cu composite material.
[0143] (3) The C / Cu composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment. The carbonization temperature is 1000°C, the single carbonization treatment time is 40-60h, and the carbonization pressure is 0.1MPa. After two cycles of impregnation / curing / carbonization treatment, the density reaches 2.0-4.0 / cm 3 The specific properties of the metal type carbon fiber composite material carbon slider are shown in Table 2 and Table 3.
[0144] Comparative Example 8
[0145] The density is 0.7g / cm 3 , a 2.5D carbon fiber copper mesh needle-punched integral felt with added carbon nanotubes is used as a preform, and a metal-type carbon fiber composite carbon slider is prepared through a chemical vapor deposition process and a three-time asphalt impregnation-carbonization process.
[0146] The metal carbon fiber composite material carbon slider in this comparative example is mainly prepared by the following steps:
[0147] (2) First, a portion of PAN-type T700 (12K) carbon fiber bundles produced by Toray Co., Ltd. of Japan is woven into a non-woven fabric, and another portion of the T700 carbon fiber bundles is cut into short fibers of 30-100 mm in length, and dispersed together with copper wire (diameter 10 μm), graphite powder (150 μm), and carbon nanotubes (diameter 20 nm) to form a mesh. Secondly, 0° non-woven carbon cloth, carbon fiber mesh, copper mesh, 90° non-woven carbon cloth, carbon fiber mesh, copper mesh, and 0° non-woven carbon cloth are cyclically stacked in sequence, and copper wire and / or carbon fiber bundles are introduced perpendicular to the layering direction by a relay needle punching method to form a non-woven fabric with a volume content of 5-15%, a mesh with a volume content of 5-15%, a copper mesh and / or copper wire with a volume content of 5-30%, and a density of 0.7 g / cm 3 Composite felt body.
[0148] (2) Using propylene as the carbon source gas and hydrogen as the diluent gas, the volume ratio of natural gas to hydrogen is 1:2, and thermal gradient chemical vapor deposition is used to deposit pyrolytic carbon on the preform at 1000°C. After deposition for 120 hours, the material is rotated 90° with the center line of the length as the axis, and then deposited for another 230 hours to obtain a C / Cu composite material.
[0149] (3) The C / Cu composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, the carbonization furnace is transferred to carbonization treatment, the carbonization temperature is 1000°C, the single carbonization treatment time is 40-60h, and the carbonization pressure is 0.1MPa. After three cycles of impregnation / curing / carbonization treatment, the density reaches 2.0-4.0 / cm 3 The specific properties of the metal type carbon fiber composite material carbon slider are shown in Table 2 and Table 3.
[0150] In the process of preparing carbon fiber preforms by relay needle punching, carbon nanotubes are difficult to disperse due to their fine particle size, and many of them leak out from the felt.
[0151] Embodiment 1:
[0152] The density is 0.35g / cm 3 The fiber needle-punched integral felt was used as a preform, and a density of 1.6 g / cm was prepared by chemical vapor deposition process. 3 The C / C composite material with a density of 1.9 g / cm was prepared through three asphalt impregnation-carbonization processes. 3 The C / C composite material was subjected to 2300℃ high temperature heat treatment and machining to obtain pure carbon fiber sliders.
[0153] The pure carbon fiber slider in this embodiment is mainly prepared by the following steps:
[0154] (1) PAN type T700 (12K) carbon fiber produced by Toray Co., Ltd. of Japan is used to make a mesh and a flat cloth, and the mass ratio of the flat cloth to the mesh is ensured to be 8:2. A single layer of 0° flat cloth, a mesh layer, a 90° flat cloth, a mesh layer, and graphite (150 μm, an addition amount of 10 wt%) are cyclically stacked in sequence, and then a relay needle punching method is used to make a density of 0.35 g / cm 3 Carbon fiber preform.
[0155] (2) The preform is subjected to a high temperature heat treatment at 1600°C in an argon protective atmosphere using a designed graphite tool. The whole process takes 8 hours. The protective atmosphere is argon and the pressure is slightly positive (i.e., slightly exceeding the 0 scale of the vacuum pressure gauge).
[0156] (3) Natural gas was used as the carbon source gas and hydrogen was used as the diluent gas. The volume ratio of natural gas to hydrogen was 1:3. The preform was deposited with pyrolytic carbon at 850°C by alternating chemical vapor deposition. After deposition for 4 hours, the C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 4 hours. The temperature was then raised to 1020°C at a rate of 10°C / min, and the deposition was continued for 50 hours. The C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 50 hours. Finally, the temperature was raised to 1080°C at a rate of 10°C / min, and the deposition was continued for 100 hours. The C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 100 hours. The obtained preform had a density of 1.6 g / cm 3 C / C composite materials.
[0157] (4) The C / C composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment. The carbonization temperature is 1000°C, the single carbonization treatment time is 40-60h, and the carbonization pressure is 0.1MPa. After two cycles of impregnation / curing / carbonization treatment, the product density reaches 1.85g / cm 3 .
[0158] (5) The obtained product was placed in a high-temperature heat treatment furnace and heat treated at 2300°C for 6 hours with argon as the protective gas to obtain an in-situ generated carbon nanotube pure carbon fiber slider. The specific properties are shown in Tables 2 and 3.
[0159] Embodiment 2:
[0160] The density is 0.4g / cm3 The fiber needle-punched integral felt was used as a preform, and a density of 1.6 g / cm was prepared by chemical vapor deposition process. 3 The C / C composite material with a density of 1.9 g / cm was prepared through three asphalt impregnation-carbonization processes. 3 The C / C composite material was subjected to 2300℃ high temperature heat treatment and machining to obtain pure carbon fiber sliders.
[0161] The pure carbon fiber slider in this embodiment is mainly prepared by the following steps:
[0162] (1) PAN type T700 (12K) carbon fiber produced by Toray Co., Ltd. of Japan is used to make a mesh and a flat cloth, and the mass ratio of the flat cloth to the mesh is ensured to be 8:2. A single layer of 0° flat cloth, a mesh layer, a 90° flat cloth, a mesh layer, and graphite (150 μm, an addition amount of 10 wt%) are cyclically stacked in sequence, and then a relay needle punching method is used to make a density of 0.4 g / cm 3 Carbon fiber preform.
[0163] (2) The preform is subjected to a high temperature heat treatment at 1600°C in an argon protective atmosphere using a designed graphite tool. The whole process takes 8 hours. The protective atmosphere is argon and the pressure is slightly positive (i.e., slightly exceeding the 0 scale of the vacuum pressure gauge).
[0164] (3) Natural gas was used as the carbon source gas and hydrogen was used as the diluent gas. The volume ratio of natural gas to hydrogen was 1:3. The preform was deposited with pyrolytic carbon at 850°C by alternating chemical vapor deposition. After deposition for 4 hours, the C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 4 hours. The temperature was then raised to 950°C at a rate of 10°C / min, and the deposition was continued for 60 hours. The C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 60 hours. Finally, the temperature was raised to 1100°C at a rate of 10°C / min, and the deposition was continued for 100 hours. The C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 100 hours. The obtained preform had a density of 1.6 g / cm 3 C / C composite materials.
[0165] (4) The C / C composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, it is transferred to a carbonization furnace for carbonization treatment. The carbonization temperature is 1000°C, the single carbonization treatment time is 40-60h, and the carbonization pressure is 0.1MPa. After three cycles of impregnation / curing / carbonization treatment, the product density reaches 1.85g / cm 3.
[0166] (5) The obtained product was placed in a high-temperature heat treatment furnace and heat treated at 2300°C for 6 hours with argon as the protective gas to obtain an in-situ generated carbon nanotube pure carbon fiber slider. The specific properties are shown in Tables 2 and 3.
[0167] Embodiment 3:
[0168] The density is 0.6g / cm 3 The 2.5D carbon fiber copper mesh needle-punched integral felt is used as a preform, and a metal-type carbon fiber composite carbon slider is prepared through a chemical vapor deposition process and two asphalt impregnation-carbonization processes.
[0169] The metal carbon fiber composite material carbon slider in this embodiment is mainly prepared by the following steps:
[0170] (1) First, a portion of PAN type T700 (12K) carbon fiber bundles produced by Toray Co., Ltd. of Japan is woven into a non-woven fabric, and another portion of the T700 carbon fiber bundles is cut into short fibers of 30-100 mm in length, and dispersed together with copper powder and graphite powder to form a mesh. Secondly, 0° non-woven carbon cloth, carbon fiber mesh, copper mesh, 90° non-woven carbon cloth, carbon fiber mesh, copper mesh, and 0° non-woven carbon cloth are cyclically stacked in sequence, and copper wire and / or carbon fiber bundles are introduced perpendicular to the layering direction by a relay needle punching method to form a non-woven fabric with a volume content of 5-15%, a mesh with a volume content of 5-15%, a copper mesh and / or copper wire with a volume content of 5-30%, and a density of 0.6 g / cm 3 Composite felt body.
[0171] (2) Natural gas was used as the carbon source gas and hydrogen was used as the diluent gas. The volume ratio of natural gas to hydrogen was 1:3. The preform was deposited with pyrolytic carbon at 850°C by alternating chemical vapor deposition. After deposition for 4 hours, the C / Cu composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 4 hours. The temperature was then raised to 1020°C at a rate of 10°C / min and deposited for 50 hours. The C / Cu composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 50 hours. Finally, the temperature was raised to 1080°C at a rate of 10°C / min and deposited for 100 hours. The C / Cu composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 100 hours. The obtained preform had a density of 1.6 g / cm 3 C / C composite materials.
[0172] (4) The C / Cu composite material is placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt is used as the impregnating agent and a high-pressure impregnation process is adopted. Before impregnation, the sample should be preheated, the impregnation temperature is 60°C, the impregnation pressure is 2MPa, and the holding time is 1.5h. After that, the temperature is raised to 250°C and kept warm for about 3h for curing. After curing, the carbonization furnace is transferred to carbonization treatment, the carbonization temperature is 1000°C, the single carbonization treatment time is 40-60h, and the carbonization pressure is 0.1MPa. After two cycles of impregnation / curing / carbonization treatment, the product density reaches 2.0-4.0g / cm 3 , the specific performance is shown in Table 2 and Table 3.
[0173] Embodiment 4:
[0174] The density is 1.0g / cm 3 The 2.5D carbon fiber copper mesh needle-punched integral felt is used as a preform, and a metal-type carbon fiber composite carbon slider is prepared through a chemical vapor deposition process and a three-time asphalt impregnation-carbonization process.
[0175] The metal carbon fiber composite material carbon slider in this embodiment is mainly prepared by the following steps:
[0176] (1) First, a portion of PAN type T700 (12K) carbon fiber bundles produced by Toray Co., Ltd. of Japan is woven into a non-woven fabric, and another portion of the T700 carbon fiber bundles is cut into short fibers of 30-100 mm in length, and dispersed together with copper powder and graphite powder to form a mesh. Secondly, 0° non-woven carbon cloth, carbon fiber mesh, copper mesh, 90° non-woven carbon cloth, carbon fiber mesh, copper mesh, and 0° non-woven carbon cloth are cyclically stacked in sequence, and copper wire and / or carbon fiber bundles are introduced perpendicular to the layering direction by a relay needle punching method to form a non-woven fabric with a volume content of 5-15%, a mesh with a volume content of 5-15%, a copper mesh and / or copper wire with a volume content of 5-30%, and a density of 1.0 g / cm 3 Composite felt body.
[0177] (2) Natural gas was used as the carbon source gas and hydrogen was used as the diluent gas. The volume ratio of natural gas to hydrogen was 1:3. The preform was deposited with pyrolytic carbon at 850°C by alternating chemical vapor deposition. After deposition for 4 hours, the C / Cu composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 4 hours. The temperature was then raised to 950°C at a rate of 10°C / min and deposited for 60 hours. The C / C composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 60 hours. Finally, the temperature was raised to 1100°C at a rate of 10°C / min and deposited for 100 hours. The C / Cu composite material was rotated 90° with the center line of the length as the axis, and the deposition was continued for 100 hours. The density of the obtained composite material was 2.0 g / cm 3 C / Cu composite materials.
[0178] (3) The C / Cu composite material was placed in a vacuum-pressure impregnation tank using the designed graphite tooling, and asphalt was used as the impregnating agent and a high-pressure impregnation process was adopted. Before impregnation, the sample should be preheated, the impregnation temperature was 60°C, the impregnation pressure was 2MPa, and the holding time was 1.5h. After that, the temperature was raised to 250°C and kept warm for about 3h for curing. After curing, the carbonization furnace was used for carbonization treatment. The carbonization temperature was 1000°C, the single carbonization treatment time was 40-60h, and the carbonization pressure was 0.1MPa. After three cycles of impregnation / curing / carbonization treatment, the density reached 2.8g / cm 3 The specific properties of the metal type carbon fiber composite material carbon slider are shown in Table 2 and Table 3.
[0179] It can be seen from Table 2 and Table 3 that compared with the pure carbon fiber sliders prepared by the conventional process of Comparative Examples 1 to 4, the graphitization degree, mechanical properties, electrical conductivity and charged friction and wear properties of the pure carbon fiber sliders with in-situ carbon nanotube growth in Examples 1 and 2 are greatly improved; compared with the metal carbon fiber sliders prepared by the conventional process of Comparative Examples 5 to 8, the graphitization degree, mechanical properties, electrical conductivity and charged friction and wear properties of the metal carbon fiber sliders with in-situ carbon nanotube growth in Examples 3 and 4 are also greatly improved. In addition, because the pure carbon fiber sliders with in-situ carbon nanotube growth have undergone high-temperature graphitization treatment of 1000°C pitch carbonization to 2000°C or more, while the metal carbon fiber sliders with in-situ carbon nanotube growth have only undergone 1000°C pitch carbonization treatment, the graphitization degree of the pure carbon fiber sliders with in-situ carbon nanotube growth is much higher than that of the metal carbon fiber sliders with in-situ carbon nanotube growth.
[0180] Table 2 Mechanical properties and conductive properties of carbon fiber sliders
[0181]
[0182] Table 3 Friction and wear properties of carbon fiber sliders
[0183]
[0184]
Claims
1. An in-situ grown carbon nanotube reinforced carbon fiber composite carbon slider, characterized by: The carbon slide bar comprises a carbon fiber needle-punched integral felt, a coating layer M covering the inside and outside of the carbon fiber needle-punched integral felt, and carbon coated on M; The M includes the following four structures: Structure 1M is a carbon nanotube and carbon particles generated in situ by chemical vapor deposition, and the carbon nanotubes and carbon particles are alternately distributed. Structure 2 M is carbon nanotubes and carbon particles generated in situ by chemical vapor deposition, and the carbon particles are coated on the carbon nanotubes; Structure three: M is a carbon nanotube layer and N generated in situ by chemical vapor deposition, wherein the N is composed of carbon particles and carbon nanotubes generated in situ; the N is coated on the carbon nanotubes; Structure 4: M is a carbon nanotube layer and N generated in situ by chemical vapor deposition, wherein N is composed of carbon particles and carbon nanotubes generated in situ; the carbon nanotube layer and N are alternately distributed; The carbon coated on M is cracked carbon prepared by an impregnation carbonization process; the carbon fiber needle-punched integral felt comprises a carbon fiber braid and a conductive wear-resistant filler; The carbon fiber braided body comprises at least one of a pure carbon fiber braided body and a three-dimensional composite braided body composed of carbon fiber and metal mesh; The conductive wear-resistant filler includes graphite powder, or at least one of graphite powder and copper powder.
2. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 1, characterized in that: When preparing M, no catalyst is used.
3. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 1, characterized in that: In the carbon fiber needle-punched integral felt, the particle size of graphite particles is 50-800 μm, and the diameter of carbon fibers is 5-100 μm.
4. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 1, characterized in that: In the coating layer M, the particle size of the carbon particles A is 20-600 nm; In the coating layer M, the diameter of the carbon nanotubes is 5-30 nm and the length is 30 nm-3 μm; In the coating layer M, the thickness of a single coating layer is less than or equal to 6 μm.
5. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 1, characterized in that: When the carbon slide bar does not contain metal, the preparation method thereof comprises the following steps: Step 1 A single layer of 0° non-weft carbon cloth, carbon fiber mesh, graphite powder, short carbon fiber (30-100 mm long), a single layer of 90° non-weft carbon cloth, a carbon fiber mesh, graphite powder, and a single layer of 0° non-weft carbon cloth are sequentially stacked in a cycle, and a carbon fiber bundle is introduced perpendicular to the layering direction by a relay needle punching method to make a carbon fiber bundle with a density of 0.2-0.8 g / cm 3 2.5D carbon fiber needle-punched integral felt; Step 2 The carbon fiber needle-punched integral felt obtained in step 1 is fixed and placed in a heating furnace, and subjected to a pre-high temperature heat treatment at 1500-2100° C. under a protective atmosphere to obtain an integral felt after the pre-high temperature heat treatment; Step 3: Prepare the M layer The whole felt obtained in step 2 after the previous high-temperature heat treatment is repeatedly subjected to high- and low-temperature chemical vapor deposition, and carbon particles / carbon nanotube layers are alternately deposited on the surface of graphite particles, carbon fibers, etc., to obtain a chemical vapor deposition pure carbon fiber slider; Step 4: Asphalt impregnation-carbonization treatment The chemical vapor deposition pure carbon fiber slider obtained in step 3 is machined according to the designed size, and after reserving the processing allowance, it is asphalt impregnated-carbonized until the density is 1.7-2.0 g / cm 3 High-density impregnation-carbonization treatment slide material; Step 5 The impregnation-carbonization treated slide obtained in step 4 is subjected to post-high temperature graphitization treatment to obtain an in-situ grown carbon nanotube reinforced pure carbon fiber carbon slide; When the carbon slide contains metal, the preparation method thereof comprises the following steps: Step A A single layer of 0° non-weft carbon cloth, carbon fiber mesh, graphite powder, copper material, a single layer of 90° non-weft carbon cloth, carbon fiber mesh, graphite powder, copper material, and a single layer of 0° non-weft carbon cloth are sequentially stacked in a cycle, and a carbon fiber bundle is introduced perpendicular to the layering direction by a relay needle punching method to prepare a 2.5D carbon fiber composite material needle-punched integral felt with a density of 0.6 to 2.6 g / cm3; Step B Preparation of M layer The carbon fiber composite needle-punched integral felt obtained in step 1 is fixed and placed in a heating furnace, and high and low temperature chemical vapor deposition is repeated multiple times to alternately deposit carbon particles / carbon nanotube layers on the surfaces of graphite particles, carbon fibers, etc., to obtain a chemical vapor deposition metal type carbon fiber composite sliding strip having a density 1.5-2.2 times that of the integral felt in step A; Step C: Asphalt impregnation-carbonization treatment The chemical vapor deposited pure carbon fiber slider obtained in step B is machined according to the designed size, and after reserving the processing allowance, it is asphalt impregnated and carbonized until a high-density impregnated and carbonized in-situ grown carbon nanotube reinforced metal carbon fiber composite carbon slider with a density of 1.02-1.15 times that of the one obtained in step 2 is obtained.
6. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 5, characterized in that: The copper material is selected from copper powder, copper mesh and short copper wire. In the 2.5D carbon fiber needle-punched integral felt, the mass percentage of graphite powder is 1% to 10%; the mass percentage of copper material is 10-90%.
7. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 5, characterized in that: When preparing the M layer, The in-situ chemical vapor deposition temperature is 850℃~1100℃; The in-situ chemical vapor deposition time is 83 to 420 hours; The carbon source gas used is selected from at least one of propylene, natural gas and methane. The diluent gas used is selected from at least one of nitrogen and hydrogen. The volume ratio of the carbon source gas to the dilution gas is 0.8-1.2:2.8-3.
2.
8. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 5, characterized in that: When preparing the M layer, in-situ vapor deposition at different temperatures is performed by temperature alternation, including the following steps: (1) First, heat to 850-950℃ and keep warm for 3-20h. (2) Raise the temperature to 950-1050°C and keep it at this temperature for 50-200 hours. (3) Finally, raise the temperature to 1080-1100°C and keep it at this temperature for 30-200 hours.
9. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 5, characterized in that: The protective atmosphere is selected from one of argon atmosphere and nitrogen atmosphere. During the pre-high temperature treatment, the control time is 3-10h. During the pre-high temperature treatment, the pressure in the furnace is controlled to be 0.101-0.11MPa; In the post-high temperature pre-treatment: The post-high temperature graphitization treatment temperature is 2000-2400°C. The post-high temperature graphitization treatment time is 5 to 10 hours. The post-high temperature graphitization treatment protective atmosphere is selected from one of an argon atmosphere and a nitrogen atmosphere. The post-high temperature graphitization treatment furnace pressure is 0.12 MPa.
10. The in-situ grown carbon nanotube reinforced carbon fiber composite material carbon slider according to claim 5, characterized in that: The asphalt impregnation-carbonization treatment comprises the following steps; After the preparation of the M layer is completed, the obtained sample is placed in an asphalt impregnation liquid at 40-80°C, and is impregnated for 1-3 hours by pressurized impregnation. The temperature is then raised to 220-260°C for curing for 2.5-3.5 hours, and the impregnation pressure is 1.5 MPa. After the curing is completed, the carbonization treatment is carried out at a carbonization temperature of 1000°C, a single carbonization treatment time of 40-60 hours, and a carbonization pressure of 0.1 MPa. The impregnation / curing / carbonization treatment is repeated until a density of 1.6-2.0 g / cm is obtained. 3 The high-density C / C composite material is prepared; the polymer impregnation liquid used in the polymer impregnation-carbonization treatment is an asphalt solution.
Citation Information
Patent Citations
A kind of carbon fiber reinforced copper-based composite material and preparation method thereof
CN104388847B
A method for preparing pantograph carbon slider material using graphene oxide
CN106699181B
Preparation technology of carbon fiber enhanced carbon pantograph pan
CN109484190A
Graphene modified copper-based carbon series locomotive pantograph slide plate and preparation method thereof
CN117403090A
Mesophase pitch carbon fiber reinforced pantograph carbon slide plate and preparation method thereof
CN117658660A
